Upper and lower limb functionality and body mass index in physically active older adults - Juliana Molinari Tecchio; Cristiane Gessinger
Abstract Introduction: Aging leads to sarcopenia and functional capacity decline, compromising upper (UL) and lower limb (LL) performance of activities. Body mass index (BMI) is an important parameter for the assessment of health conditions in older adults, especially with regard to obesity, since it leads to functional limitations in terms of mobility and task performance. Objective: To investigate the potential association between UL and LL functionality and BMI in physically active older adults; and to characterize this population with regard to BMI and UL and LL functionality. Methods: The data were collected between August 2013 and April 2014. The sample comprised 371 physically active older adults. This study used secondary data from the program "PET Saúde IPA/SMS". The program interviewed older adults living in areas comprised by the Third Family Health Unit of a neighborhood in Porto Alegre/RS. This paper used questions from the "Instrumento de Avaliação Multidimensional Rápida da Pessoa Idosa" (Instrument for Rapid Multidimensional Assessment of Elderly People, in English) that had to do with UL and LL functionality, weight, height and BMI. Results and Conclusion: There was no association between UL and LL functionality and BMI in physically active older adults. More than half of the sample was overweight. Most participants had functional UL and LL. While occupation, self-perception of health as "good" and "very good", and physical activity were found to be associated with LL functionality; regular physical exercise was found to be associated with UL and LL functionality.